The Grading Process in System 1 and System 2 of Thinking: A Behavioral Economic Approach to Evaluation - Călinescu, Amalia (Integrated Journal for Research in Arts and Humanities, 2023)
The concepts of heuristics and biases underlie the decision-making process both at intuitive and rational levels, which Daniel Kahneman refers to as System 1 and System 2 of thinking. This research seeks to explore the interplay between these cognitive mechanisms and students’ grading decisions, examining the extent to which heuristics and biases can influence evaluation in the everyday process of learning and teaching. A survey was conducted, containing four grading situations that combine the experiences of reading, evaluation, and decision-making in four stages of System 1 and System 2 of thinking. The hypotheses and sub-hypotheses were tested using a quantitative approach, through a 15-item self-administered questionnaire (SAQ) in English, which collected data about the heuristics influencing Romanian students’ grading decision in four evaluative situations based on a synopsis of The Book Thief by Markus Zusak. The self-constructed questionnaire was filled in by 108 Romanian students studying for a bachelor’s, master’s, or doctoral degree in public and private universities. The data set was analyzed, using descriptive, inferential, and path-analysis methods (frequencies, percentages, measures of central tendency, t-tests, ANOVA, simple and multiple linear regression, mediation, and moderation) and one statistical program (R Studio 4.3.4.). Grade 1 (the most intuitive) can predict Grade 4 for the synopsis of The Book Thief. However, the correlation between Grades 2 + 3 and Grade 4 is much stronger than the correlation between Grade 1 and Grade 4. Furthermore, the impact of Grade 1 on Grade 4 is mediated by Grade 3 while Grade 1 has no effect on the impact of Grade 3 on Grade 4. The rational model of heuristics involved in the grading process is much stronger than the intuitive model. The study sheds light on the intricate interplay between intuition and rationality in the grading process, offering novel insights into the cognitive mechanisms that underlie decision-making.